2020
DOI: 10.21608/mjfds.2020.171473
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Potato Peel Extract as a Source of Antioxidant and Antimicrobial Substances

Abstract: Antioxidant and antimicrobial substances were extracted from potato peels by using different solvents (water and both methanol and ethanol at a concentration of 80 and 100 %). The potato peel extracts were evaluated for yield extract, antioxidants activity, total phenols and total flavonoids. The best extracts were selected for their efficacy as an antioxidant and antimicrobial. The proximate composition of dried potato peels indicated that total carbohydrates (65.47 %) were the major compound, while total lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“… 20 Ireland Anti-inflammatory Properties of potato glycoalkaloids in stimulated Jurkat and Raw 264.7 mouse macrophages Solanum tuberosum Ethyl acetate fraction and methanol fraction Glycoalkaloid compounds by Waters acquity method No (anti-inflammatory activity) Anti-inflammatory activity with human Jurkat T cell and RAW 246.7 mouse macrophages by biomarker IL2 and IL8 Using doses 5, 10, 25 µ/mL Glycoalkaloid Compounds from the potato peel fraction have anti-inflammatory effects, for example, diosgenin which can inhibit the inflammatory response 6 Helal et al, 2020. 10 Egypt Evaluation of potato peel extract as a source of anti-oxidant and antimicrobial substances Solanum tuberosum Water, methanol, and ethanol (80 and 100%) extracts from potato peels Phenol and flavonoid compounds (vanillic and hesperidin) No (anti-microbial and anti-oxidant activity) Anti-oxidant activity with DPPH and anti-microbial with Bacillus subtilis ATCC 6633, Staphylococcus aureus ATCC 29213, E. coli ATCC 25922, Salmonella t. ATCC14028, and C. albicans ATCC 10231 Dose 70 µL (200 and 400 ppm), potato peel methanol extract 400 ppm was more effective in inhibiting gram-positive, gram-negative bacteria and Candida albicans than ampicillin (control) 7 Chauhan, 2014. 11 India Study of anti-oxidant potential of Solanum tuberosum peels extract Solanum tuberosum Ethyl acetate and methanol extract from potato peel Phenolic compounds (gallic acid) No (anti-oxidant activity) Anti-oxidant activity with DPPH method and Nitric oxide activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 20 Ireland Anti-inflammatory Properties of potato glycoalkaloids in stimulated Jurkat and Raw 264.7 mouse macrophages Solanum tuberosum Ethyl acetate fraction and methanol fraction Glycoalkaloid compounds by Waters acquity method No (anti-inflammatory activity) Anti-inflammatory activity with human Jurkat T cell and RAW 246.7 mouse macrophages by biomarker IL2 and IL8 Using doses 5, 10, 25 µ/mL Glycoalkaloid Compounds from the potato peel fraction have anti-inflammatory effects, for example, diosgenin which can inhibit the inflammatory response 6 Helal et al, 2020. 10 Egypt Evaluation of potato peel extract as a source of anti-oxidant and antimicrobial substances Solanum tuberosum Water, methanol, and ethanol (80 and 100%) extracts from potato peels Phenol and flavonoid compounds (vanillic and hesperidin) No (anti-microbial and anti-oxidant activity) Anti-oxidant activity with DPPH and anti-microbial with Bacillus subtilis ATCC 6633, Staphylococcus aureus ATCC 29213, E. coli ATCC 25922, Salmonella t. ATCC14028, and C. albicans ATCC 10231 Dose 70 µL (200 and 400 ppm), potato peel methanol extract 400 ppm was more effective in inhibiting gram-positive, gram-negative bacteria and Candida albicans than ampicillin (control) 7 Chauhan, 2014. 11 India Study of anti-oxidant potential of Solanum tuberosum peels extract Solanum tuberosum Ethyl acetate and methanol extract from potato peel Phenolic compounds (gallic acid) No (anti-oxidant activity) Anti-oxidant activity with DPPH method and Nitric oxide activity.…”
Section: Resultsmentioning
confidence: 99%
“…The reviewed articles predominantly reported on the antioxidant activity of potato peel extract preparations. [8][9][10][11][12][13][14][15][16] The high antioxidant activity of potato peels can be attributed to the presence of vitamin C, flavonoids, polyphenols, and anthocyanins. [4][5][6] Vitamin C is an antioxidant that produces collagen, which is vital for maintaining skin health and facilitating wound healing by stimulating fibroblast formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proximate analysis of the raw PPW revealed that it contained 10.29% moisture, 8.81% ash, 0.44% crude fat, 15.45% crude protein, 4.4% crude fiber, and 65.01% carbohydrates on dry weight basis, as shown in Table 3 . A protein content of 10.54% in dried potato peels has been reported [ 34 , 35 ]. Another research report has recorded an almost similar level of fat from the potato peels, which was 0.28% [ 36 ].…”
Section: Resultsmentioning
confidence: 99%